Matrimonial property between jurisprudence and reality - Zaghloul, Saad Gomaa Gomaa; Ahmed, Ahmed Ramadan Mohamed; Bakar, Marina Abu; Zainon, Masyitah Mohd (Linguistics and Culture Review, 2021)
Matrimonial property plays an important role in achieving family stability and in building the society. Therefore, due attention must be given to the nature of matrimonial property, how it is managed and the guidelines governing it when disputes about it arise to protect the financial rights of both spouses from any damage that can threaten the stability and development of the society. Laws have been enacted in some Muslim countries like Tunisia and Malaysia to give a wife the right to have a share in the property acquired by her husband during the marriage. Thus, all the above prompted us to participate in highlighting this issue that was not discussed by classical jurists and to examine the types of wealth acquired during marriage and the ruling of each type in this research paper.